"The problem is bigger than us": Grappling with educational inequity in TeachFirst New Zealand. (November 2017) - Crawford-Garrett, Katherine
Abstract: This article utilizes phenomenological research approaches to trace the experiences of participants within TeachFirst New Zealand (TFNZ), a member of the global network, Teach for All, as they grapple with their role in addressing educational inequality on a national scale. Specifically, I argue that TFNZ participants struggled within and against "thin equity" (Cochran-Smith et al., 2016) explanations of persistent inequality by focusing on how they (1) understand their role as individual teachers working in an educational system marked by a history of colonization and systemic racism, and (2) grapple with the ability of an individual teacher to effect lasting change. Highlights: Research on Teach for All must address the lived experiences of the participants. Neoliberalism presents challenges for participants, specifically individualism. TeachFirst participants need opportunities to grapple with social inequality.